Clinical outcomes in management of unstable distal radius fractures treated with external fixation and internal fixation: a prospective comparative study - Dash, Sunil Kumar; Sharma, Manish Kumar; Mishra, Sanket; Marandi, Hatia; Das, Aurobinda; Satapathy, Deepankar; Ahmed, Syed S. (International Journal of Research in Orthopaedics, 2017)
Background: Management of Distal Radius fracture that are inherently unstable is still a matter of debate. There is no conclusive evidence that support one surgical fixation method over another. An attempt was made to analyze patients treated with Ex-Fix and Internal-Fixation for unstable distal radius fractures and evaluate the clinical efficacy of Ex-fix using principles of ligamentotaxis and Internal-fixation and compare functional recovery, fracture healing time and complications. Methods: A prospective trial was undertaken at our hospital with 35 patients,all aged >20 yrs with closed distal radius fracture and divided into two groups: group I (Ex-fix with or without percutaneous k-wire, and JESS) and group II (Int-Fixation) including 14 and 21 patients, respectively. Periodic clinical examination and x-ray review was carried out to find out fracture union, and functional assessment. Patients were followed up for 1 year, 6 months average. Results: Group I consumed significant less operative time, fluoroscopic exposure, reduced hospital stay, quicker post-operative pain relief. Quick DASH score were significantly high in elderly treated with Ex-Fix in comparison to young in which DASH score was higher with internal-fixator. Functional recovery was early with int-fixation but post-operative wrist stiffness was also higher. 2 cases of delayed wound healing &1 case of pin tract infection with ex-fix application was observed. Conclusions: Internal-fixation remains the treatment of choice for unstable distal radius fracture involving the articular surface and in the young, while ext-fixation can be considered as a primary treatment modality in the extra-articular fractures in young or even intra-articular fractures in the elderly.